The sleep-leaping kangaroo - Pape, Donna (Lugg).; Eaton, Tom (Champaign, Ill., Garrard Pub. Co., 1973)
Kara Kangaroo tries several cures for sleep-jumping until she finally devises a method to weight herself down.
13 39
Keywords: Kangaroos -- Fiction